2018
DOI: 10.1177/0954008318780218
|View full text |Cite
|
Sign up to set email alerts
|

Electrical, thermal, and dielectric studies of ionic liquid-based polymer electrolyte for photoelectrochemical device

Abstract: In this work, solution cast method was adapted for the preparation of 1-ethyl-3-methylimidazolium dicyanamide (EMImDCN)-doped solid polymer electrolyte. Optimum composition of polymer electrolyte (polyethylene oxide + sodium iodide) was treated as the host polymer. The ionic conductivity was further enhanced by adding low-viscosity ionic liquid (IL) EMImDCN. Electrical, thermal, dielectric, and photoelectrochemical properties of polymer host and IL-doped solid polymer electrolyte (ILDPE) are presented in detai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…cations and anions) while a decrease in ionic conductivity is generally defined by multiple charge formation. 9 However polymer electrolyte systems with two maxima are rather scanty. Lakshmi and Chandra 3 reported two maxima in an ion-conducting system where first maxima are defined by cation while second maxima are associated with anions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…cations and anions) while a decrease in ionic conductivity is generally defined by multiple charge formation. 9 However polymer electrolyte systems with two maxima are rather scanty. Lakshmi and Chandra 3 reported two maxima in an ion-conducting system where first maxima are defined by cation while second maxima are associated with anions.…”
Section: Resultsmentioning
confidence: 99%
“…where Z ″ is the imaginary part of impedance at the lowest frequency. 9 15 The value of specific capacitance we have calculated using low-frequency impedance is 24.8 F g −1 .…”
Section: Resultsmentioning
confidence: 99%
“…1mgcm -1 of electrode material was coated onto the cc (the homogenous mixture of binder to rGO ratio was fixed at 90:10) as reported in literature. 4 Additionally, we have fabricated our DSSC using doctor blades and spin coating method as reported in the literature. 14…”
Section: Fabrication Of Edlc/dsscmentioning
confidence: 99%
“…incorporated with PEO have been reported several times which shows that crystallinity of the polymer decreases with the increase in the wt% of salts. 4 For the last decades, our group is focused on developing highly conducting polymer electrolytes based on low viscosity ionic liquids (IL) doped polymer electrolytes. A variety of ILs is doped in polyethers to explore the enhancement in ionic conductivity in these polyethers which may be further applied in electrochemical devices.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 Various attempts have been made by many workers to achieve higher ionic conductivity values in polymer electrolytes, that is, the use of increasing the amount of salt and plasticizers, blending of polymers, the formation of cross-linked networks, and the use of fillers in polymer electrolytes and polymer gel electrolytes. 7 15 Out of these methods, the addition of plasticizer is one of the most effective methods to enhance the ionic conductivity values by maximizing ion dissociation and amorphicity of polymer electrolyte. Also different authors have reported earlier that the use of plasticizers facilitates improvement in the ionic conductivity by the dissociation of ion aggregates, increase in the amorphous content, lowering the glass transition temperature ( T g ), and softening of polymer electrolytic films.…”
Section: Introductionmentioning
confidence: 99%